OPTIMASI DAN MODIFIKASI METODE KOLEKSI STOMATA TANAMAN KACANG PANJANG (Vigna sesquipedalis L. Fruwith) MENGGUNAKAN METODE STOMATAL PRINTING - Shalati Febjislami; Sanna Paija Hasibuan (Universitas Gunadarma, 2023)
Long beans are a popular horticultural crop known for their nutritious green vegetables, particularly the young fruit and leaves. There have been numerous studies conducted on the cultivation and breeding of long beans. However, further research is required to obtain more data on preparation of stomata imprint and morphology. This study aims to examine the optimization and modification of stomatal printing methods on long bean plants to produce imprint in a short time with clear quality. The experiment was carried out from April to June 2021 at the Plant Physiology Laboratory, Department of Agronomy, Faculty of Agriculture, Andalas University, using stomatal printing method on long bean plant leaves. The experiment consisted of two stages: first, the removal of cuticle and trichome; and second, the method of application of the printing material and the drying time of the imprint. Based on the experimental results, it was found that stomatal imprint of long bean plants could be obtained without having to remove the cuticle or trichomes. Applying a thin layer of nail polish for at least 20 minutes can produce 100% imprinted stomata, while using a thin layer of adhesive glue takes at least 10 minutes. Adhesive glue can be used as an alternative to nail polish with faster drying time and clearer imprint results in the stomatal printing method. The stomata number of long bean plants is enormous, with a density of 184-237 per mm2. The stomata type of long bean plants is parasitic.